Effect of evolocumab on the progression of intraplaque neovascularization of the carotid based on contrast-enhanced ultrasonography (EPIC study): A prospective single-arm, open-label study - Chen, Ju; Zhao, Faming; Lei, Chengbin; Qi, Tianjun; Xue, Xin; Meng, Yuan; Zhang, Wenzhong; Zhang, Hui; Wang, Jian; Zhu, Haijun; Cheng, Cheng; Wang, Qilei; et al. (Frontiers in Pharmacology, 2023)
Abstract Background and Purpose The aim of this study was to explore the effect of half a year of evolocumab plus moderate-intensity statin treatment on carotid intraplaque neovascularization (IPN) and blood lipid levels. Methods A total of 31 patients with 33 carotid plaques who received evolocumab plus statin treatment were included. Blood lipid levels, B-mode ultrasound and contrast-enhanced ultrasonography (CEUS) at baseline and after half a year of evolocumab plus statin therapy were collected. The area under the curve (AUC) reflected the total amount of acoustic developer entering the plaque or lumen within the 180 s measurement period. The enhanced intensity reflected the peak blood flow intensity during the monitoring period, and the contrast agent area reflected the area of vessels in the plaques. Results Except for high-density lipoprotein cholesterol (HDL-c), all other lipid indices decreased. Compared with baseline, low-density lipoprotein cholesterol (LDL-c) decreased by approximately 57% (p<0.001); total cholesterol (TC) decreased by approximately 34% (p<0.001); small dense low-density lipoprotein (sd-LDL) decreased by approximately 52% (p<0.001); and HDL-c increased by approximately 20% (p<0.001). B-mode ultrasonography showed that the length and thickness of the plaque and the hypoechoic area ratio were reduced (p<0.05). The plaque area, calcified area ratio, and lumen cross-sectional area changed little (p>0.05). CEUS revealed that the area under the curve of plaque/lumen (AUC (P/L)) decreased from 0.27±0.13 to 0.19±0.11 (p<0.001). The enhanced intensity ratio of plaque/lumen (intensity ratio (P/L)) decreased from 0.37±0.16 to 0.31±0.14 (p=0.009). The contrast agent area in plaque/area of plaque decreased from 19.20±13.23 to 12.66±9.59 (p=0.003). The neovascularization score decreased from 2.64±0.54 to 2.06±0.86 (p<0.001). Subgroup analysis based on statin duration (<6 months and ≥6 months) showed that there was no significant difference in the AUC (P/L) or intensity ratio (P/L) at baseline or after half a year of evolocumab treatment. Conclusion This study found that evolocumab combined with moderate-intensity statins significantly improved the blood lipid profile and reduced carotid IPN.